2020
DOI: 10.3389/fonc.2020.541281
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach Validates Genetic Risk Factors for Late Toxicity After Prostate Cancer Radiotherapy in a REQUITE Multi-National Cohort

Abstract: Background: REQUITE (validating pREdictive models and biomarkers of radiotherapy toxicity to reduce side effects and improve QUalITy of lifE in cancer survivors) is an international prospective cohort study. The purpose of this project was to analyse a cohort of patients recruited into REQUITE using a deep learning algorithm to identify patient-specific features associated with the development of toxicity, and test the approach by attempting to validate previously published genetic risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Genetic variants and biomarkers are gaining importance in the prediction of the development of adverse effects following RT [8]. Recently, replicated genetic associations for adverse reactions to RT were reported [11]. Genetic biomarkers could help to identify high-risk on toxicity patients and that could allow radiotherapists to personalize treatments for patients for which extra care should be taken to decrease the dose to the bladder or urethra.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variants and biomarkers are gaining importance in the prediction of the development of adverse effects following RT [8]. Recently, replicated genetic associations for adverse reactions to RT were reported [11]. Genetic biomarkers could help to identify high-risk on toxicity patients and that could allow radiotherapists to personalize treatments for patients for which extra care should be taken to decrease the dose to the bladder or urethra.…”
Section: Resultsmentioning
confidence: 99%
“…Here we aim to identify the combined effect of several SNPs on late radiotherapy toxicity and propose a novel scoring method to summarise genetic information that incorporates epistatic effects. Our work builds on the results of a previous study where SNPs identified as affecting risk of late radio-induced toxicity were confirmed by external independent validation [8]. There, the authors considered a pool of 43 SNPs associated with late radiotherapy toxicity from the literature.…”
mentioning
confidence: 76%
“…SNPs selected for SNP-allele sets learning for each toxicity endpoint. The SNPs in the table are those identified as relevant in[8] to separate between patients with/without late toxicity symptoms. .. Urinary Frequency grade !…”
mentioning
confidence: 99%
“…Similarly, the REQUITE project is a trial to validate predictive models and biomarkers of radiotherapy toxicity to reduce side-effects and improve quality of life in cancer survivors (70). In the latter cohort of patients, Massi et al (71) isolated, by means of a deep learning approach, eight SNP signatures that could identify patients most likely to experience adverse effects after radiotherapy for prostate cancer. The genetic susceptibility to develop RP could also have a cancerspecific prognostic value.…”
Section: Increased Understanding Of Pathogenesis and Predictive Signatures Supporting Possible Therapeutic Implicationsmentioning
confidence: 99%